Solving the problems of daylighting and tradition continuity in a reconstructed vernacular building - Šiožinytė, Eglė; Antuchevičienė, Jurgita (Journal of Civil Engineering and Management, 2013)
Seeking for saving traditional forms, sizes, proportions and other features of vernacular architecture and satisfying norms for a contemporary building sometimes is not an easy task. The presented case study about indoor daylighting in Lithuanian vernacular architecture shows the existing problem. The authors of the article suggest possible variants of how to improve daylighting in vernacular buildings. The aim of the conducted research is to propose a rational solution to the problem using multiple criteria assessment. Alternative variants can be characterized by a number of quantitative and qualitative criteria. Thus, for ranking alternatives and achieving the most rational solution, the use of the Analytic Hierarchy Process (AHP) to evaluate the relative importance of criteria as well as the application of Multiple Criteria Decision Making (MCDM) methods are put forward. The case study presents possible alternatives for improving daylighting in the reconstructed building and simultaneously analyses the process of saving the features of vernacular architecture applying the AHP for weighting criteria and Complex Proportional Assessment (COPRAS), Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) and Weighted Aggregated Sum Product Assessment (WASPAS) for ranking alternative solutions. It is estimated that the utility degree of the best ranked alternative exceeds the further ranked alternatives from 29 to 49 percent.